PENYEBARAN AGAMA ISLAM OLEH SEKH JAMBU MANGLID PADA ABAD KE-16 DI DESA AIRNANINGAN - Evi Kusmiana; Iskandar Syah; Muhammad Basri (FKIP UNIVERSITAS LAMPUNG, 2013)
This research aims to know state of the Islam Spread Sekh Jambu Manglid The Century-16 Sub In Village Airnaningan Airnaningan Tanggamus District.The method is the Deskriptif research methods. The collection data technique used wawancara an literation study, while the analysis of the data used is analysis of qualitative data. The results showed that the ability of the change in mindset of the people about the religion of Islam, after efforts were made by Sekh Jambu Manglid in spreading the religion of Islam in the village Airnaningan. In Sekh Jambu Manglid spread using two (2) methods of the art methods and methods of education. Through art methods Sekh Jambu Manglid using puppet art and music, while through educational methods Sekh Jambu Manglid build teaching facilities to build a boarding school called Al-Qodir.Kata kunci : kesenian, wayang dan pendidikan